Similar complex kinematics within two massive, filamentary infrared dark clouds. Issue 4 (22nd January 2018) - Barnes, A T; Henshaw, J D; Caselli, P; Jiménez-Serra, I; Tan, J C; Fontani, F; Pon, A; Ragan, S
Abstract: Infrared dark clouds (IRDCs) are thought to be potential hosts of the elusive early phases of high-mass star formation. Here, we conduct an in-depth kinematic analysis of one such IRDC, G034.43+00.24 (Cloud F), using high sensitivity and high spectral resolution IRAM-30m N2 H +  (1–0) and C 18 O (1–0) observations. To disentangle the complex velocity structure within this cloud, we use Gaussian decomposition and hierarchical clustering algorithms. We find that four distinct coherent velocity components are present within Cloud F. The properties of these components are compared to those found in a similar IRDC, G035.39-00.33 (Cloud H). We find that the components in both clouds have high densities (inferred by their identification in N2 H + ), trans-to-supersonic non-thermal velocity dispersions with Mach numbers of ∼1.5–4, a separation in velocity of ∼3 km s −1, and a mean red-shift of ∼0.3 km s −1 between the N2 H + (dense gas) and C 18 O emission (envelope gas). The latter of these could suggest that these clouds share a common formation scenario. We investigate the kinematics of the larger-scale Cloud F structures, using lower-density-tracing 13 CO(1–0) observations. A good correspondence is found between the components identified in the IRAM-30m observations and the most prominent component in the 13 CO data. We find that the IRDC Cloud F is only a small part of a much larger structure, which appears to be an inter-arm filament of the Milky Way.